Comparative Analysis of 2022 Outbreak MPXV and Previous Clade II MPXV (2024)
The 2022–2024 outbreak of MPOX is an important worldwide public health issue that has triggered significant concerns in the scientific community. MPOX is caused by monkeypox virus (MPXV) belonging to the Poxviridae family. The study of MPXV presents a multifaceted challenge due to the diverse viral formThis study was supported by ISIDORe consortium and Agencia Estatal de Investigación.s produced by this pathogen. Notably the intracellular mature viruses (MVs) primarily contribute to localized lesions and host-to-host transmission, while the extracellular enveloped viruses (EVs) are associated with systemic infection. Clinically, MPOX manifests as a vesiculopustular rash that initially emerges on the face and trunk, subsequently spreading throughout the body, with heightened severity observed in immunocompromised individuals. Results obtained in this manuscript indicate that the 2022 outbreak MPXV has a significantly slower viral cycle compared with previous Clade II strains, with WRAIR 7-61 being more intermediate and USA 2003 producing highest viral titers. Additionally, proteomic and phospho-proteomic analysis displays differences in protein expression between these three strains. These findings highlight key differences between the current Lineage B.1 MPXV and previous strains. Further studies will be undertaken to demonstrate if these differences are important for the apparent increased human-to-human transmission mechanisms observed in the Clade IIb MPXV outbreak.